Nonlinear control of coherent absorption and its optical signal processing applications - Xomalis, Angelos (2020)
All-optical data processing continues to attract significant interest as a way to overcome the electronic signal processing bottleneck of fiber telecommunication networks. Nonlinear optical devices such as limiters and saturable absorbers rely on intensity-dependent attenuation of light. However, making such devices using intensity-dependent multiphoton dissipation processes is an issue as these make complete absorption and transmission impossible. Here, we show that nonlinear phase retardation in an optical fiber can control the dissipation of coherent light waves interacting on a thin plasmonic absorber from total absorption to perfect transmission. The fiber’s instantaneous Kerr nonlinearity and the femtosecond coherent absorption time scale make this approach ultrafast. We report proof-of-principle demonstrations of all-optical intensity discrimination, power limiting, pulse restoration, pulse splitting, and signal transfer between carrier wavelengths within a fiber circuit. Our results indicate that nonlinear control of coherent absorption can imitate and outperform saturable and multiphoton absorption in terms of bandwidth and contrast.